Analysis of the isomerism effect on the mutual solubilities of bis(trifluoromethylsulfonyl)imide-based ionic liquids with water - Martins, Mónia A.R. (2016)
The knowledge of the liquid-liquid equilibria (LLE) between ionic liquids (ILs) and water is of utmost importance for environmental monitoring, process design and optimization. Therefore, in this work, the mutual solubilities with water, for the ILs combining the 1-methylimidazolium, [C(1)im](+); 1-ethylimidazolium, [C(2)im](+); 1-ethyl-3-propylimidazolium, [C(2)C(3)im](+); and 1-butyl-2,3-dimethylimidazolium, [C(4)C(1)C(1)im](+) cations with the bis(trifluoromethylsulfonyl)imide anion, were determined and compared with the isomers of the symmetric 1,3-dialkylimidazolium bis(trifluoromethylsulfonyl)imide ([C(n)C(n)im][NTf2], with n=1-3) and of the asymmetric 1-alkyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C(n)C(1)im][NTf2], with n = 2-5) series of ILs. The results obtained provide a broad picture of the impact of the IL cation structural isomerism, including the number of alkyl side chains at the cation, on the water-IL mutual solubilities. Despite the hydrophobic behaviour associated to the [NTf2](-) anion, the results show a significant solubility of water in the IL-rich phase, while the solubility of ILs in the water-rich phase is much lower. The thermodynamic properties of solution indicate that the solubility of ILs in water is entropically driven and highly influenced by the cation size. Using the results obtained here in addition to literature data, a correlation between the solubility of [NTf2]-based ILs in water and their molar volume, for a large range of cations, is proposed. The COnductor like Screening MOdel for Real Solvents (COSMO-RS) was also used to estimate the LLE of the investigated systems and proved to be a useful predictive tool for the a priori screening of ILs aiming at finding suitable candidates before extensive experimental measurements.